Risk Financing and Financing Risks In Case of Geothermal Investments - Jenei, Tünde (International Journal of Engineering and Management Sciences, 2017)
In an investment process various sizes and types of risk arise. In project financing risk sharing is based on the assumption that the risk is to be borne by who is able to control and influence it. The article examines that project financing as a risk management technique is applicable to the treatment of geothermal investment risks.